Fibroblast growth factor 23 level modulates the hepatocyte’s alpha-2-HS-glycoprotein transcription through the inflammatory pathway TNFα/NFκB - Mattinzoli, Deborah; Li, Min; Castellano, Giuseppe; Ikehata, Masami; Armelloni, Silvia; Elli, Francesca Marta; Molinari, Paolo; Tsugawa, Koji; Alfieri, Carlo Maria; Messa, Piergiorgio (Frontiers in Medicine, 2022)
High serum levels of fibroblast growth factor 23 (FGF23) characterize chronic kidney disease (CKD) since its early stages and have been suggested to contribute to inflammation and cardiovascular disease. However, the mechanisms linking FGF23 with these pathological conditions remain still incompletely defined. The alpha-2-HS-glycoprotein (AHSG), a liver-produced anti-inflammatory cytokine, is highly modulated by inflammation itself, also through the TNFα/NFκB signaling pathway. In our previous study, we found that FGF23 modulates the production of AHSG in the liver in a bimodal way, with stimulation and inhibition at moderately and highly increased FGF23 concentrations, respectively. Methods The present study, aiming to gain further insights into this bimodal behavior, was performed in hepatocyte human cells line (HepG2), using the following methods: immunochemistry, western blot, chromatin immunoprecipitation, FISH, qRT-PCR, and gene SANGER sequencing. Results We found that FGF23 at 400 pg/mL activates nuclear translocation of NFκB, possibly increasing AHSG transcription. At variance, at 1200 pg/mL, FGF23 inactivates NFκB through the activation of two specific NFκB inhibitors (IκBα & NKIRAS2) and induces its detachment from the AHSG promoter, reducing AHSG transcription. Conclusion These results add another piece to the puzzle of FGF23 involvement in the multifold interactions between CKD, inflammation, and cardiovascular disease, suggesting the involvement of the NFκB pathway, which might represent a potential therapeutic target in CKD.